When Politicization Stops Algorithms in Criminal Justice - König, Pascal (The British journal of criminology, 2021)
The present paper sheds light on the conditions for successfully implementing pretrial risk assessment tools by looking at barriers to their implementation and, specifically, political factors that can derail this process. Drawing on theoretical assumptions about the role of agenda-setting and public discourse in policy change, we examine three US states where the implementation of pretrial tools was halted or heavily restricted. Our findings suggest that a politicization of these tools plays a central role for thwarting their implementation. This has less to do with their technical properties or performance. Rather, through reaching high-level politics, those tools are publicly linked to concerns about opacity, fairness and public safety such that it simply becomes politically safer for politicians to stick with the status quo.